Single-Layer High Gain Endfire Antenna Based on Spoof Surface Plasmon Polaritons - Liu, Leilei; Chen, Minghong; Yin, Xiaoxing (IEEE access, 2020)
A novel high gain endfire antenna based on the spoof surface plasmon polaritons (SSPP) transmission line (TL) is proposed in this paper. The antenna is designed on a groundless single metal layer inherited the advantages of SSPP. Combined with asymmetric radiation elements of SSPP TL and an elliptical director, this antenna generates endfire radiation beams with 15.75-17.5 GHz. Although the aperture is small, it has obtained a high gain from 10.5 to 12.1 dBi and a high efficiency of 95% overall the operating bandwidth. Measurement results agree well with the simulations. The advantages of single-layer, high gain and low profile make its valuable in wireless communications.